Phaenomena - Aratus, Solensis (Book collections on Project MUSE., 2010)
"After the Iliad and the Odyssey, the Phaenomena was the most widely read poem in the ancient world. Its fame was immediate. It was translated into Latin by Ovid and Cicero and quoted by St. Paul in the New Testament, and it was one of the few Greek poems translated into Arabic"--Back cover